Distal type of aortopulmonary window. Report of 4 cases. Issue 6 (June 1978) - Mori, K; Ando, M; Takao, A; Ishikawa, S; Imai, Y
Abstract : We have studied 14 patients with aortopulmonary window (10 male and 4 female, age range 1 month to 41 years). Four of these had a distal defect with characteristic haemodynamic and angiographic features. Aortopulmonary window may be classified into 3 types: type I (proximal) defects occur in the proximal part of aortopulmonary septum; type II (distal) defects occur in the distal part of the aortopulmonary septum adjacent to the right pulmonary artery; the type III defect is a combination of types I and II. In type I, injection of contrast media into the aortic root opacifies the main pulmonary trunk and then both pulmonary arteries. In type II, the right pulmonary artery is preferentially opacified simulating the finding of right pulmonary artery arising from the ascending aorta. In one case of type II, injection into the right ventricle showed preferential flow to the left pulmonary artery, because of the large shunt of unopacified blood into the right pulmonary artery, but in both types I and II the left and right pulmonary arteries are usually opacified simultaneously after injection into the main pulmonary trunk. In type I either transaortic or transpulmonary closure is the appropriate surgical procedure. In types II and III, the transaortic approach provides better exposure and facilitates the operative repair.